Acceptability Test of Rainbow Meatball as an Alternative Snack to Prevent Anemia in Adolescents - Kusmini Suprihatin; Ani Intiyati; Siti Maemonah (GLOBAL HEALTH SCIENCE GROUP, 2025)
Anemia is a health problem that can occur in all age groups ranging from toddlers to the elderly. Adolescent girls are prone to anemia due to the monthly menstrual cycle. Anemia in adolescents is defined as a state of hemoglobin (Hb) levels in the blood less and normal numbers according to sex and age groups. The incidence of anemia in East Java in 2021 showed a percentage of 57.1%. Meanwhile, the incidence of anemia in Sidoarjo district is 46.7%. In setting a diet with balanced nutrition in adolescent girls, iron intake is so important, so snack innovations with high iron content are needed.Objectives: To determine the acceptability of rainbow meatballs as an alternative iron-rich snack to prevent anemia in adolescent girlsMethods: This research design is a Pre Experiment research design with organoleptic tests on 30 adolescents aged 10-19 years as panelists with random sampling technique. The population was taken from a class of 42 students of the Diploma in Nutrition Program who had been trained. The sample was determined based on the slovin formula and 30 panelists were obtained with an alpha of 0.01. The data that has been collected will then be processed, tabulated, and interpreted, and analyzed. the data analysis technique used is the Kruskal Wallis statistical test and continued with Mann Whitney.Results: The most preferred formula and has the highest iron content is formula 3 with an average value of 4.01 and iron content of 0.41 mg each 100 g of product. The results of statistical tests using Kruskal Wallis showed significant differences in taste and appearance indicators, which then after further testing using Mann Whitney found significant differences between the 3 rainbow meatball formulas on taste and appearance indicators.Conclusions: The most preferred rainbow meatball formulation by panelists is formula 3 with an average score of 4.01. In the Kruskal Wallis statistical test, differences were found in the taste and appearance indicators. After further testing using Mann Whitney on the taste indicator, there was a significant difference between three formulation of rainbow meatballs. The formulation with the highest iron content is formula 3 with the addition of carrot extract.